(untitled) (Interdisciplinary Research in Education, 2023)
This study critically analyzed the future policy direction of special/inclusive education in Nepal. Using qualitative data collected through document analysis, interviews, and focus group discussions. This study is based on the premises of qualitative research design under the interpretative paradigm followed by critical interpretive design to analyze and interpret the field data. For this, 15 (fifteen) policy experts from Ministry of Education, Science, and Technology, Department of Education, university professors, and 11 head teachers from 6 special and 5 integrated schools, and special education council members and members of disabled related organizations were purposively selected as the informants. The establishment of the Disability Right Commission at central level would be much effective for the overall development of special/inclusive education in Nepal. It has also been found that establishment of the special/inclusive education council secretariat would contribute to further expansion of special/inclusive education service in Nepal. Development of a provincial level master plan for special/inclusive education training for stakeholders has been strongly recommended for the overall development of special education in the country. The study also suggested that future policy development and its practice is to be based on research-based evidence. It also recommended for establishment of at least one special education center and one model school in each province, and at least one support center at each local level. This study implies that a coherent policy-making is required through the consultation with the relevant stakeholders from the central, provincial, and local level in such a way that there is minimum gap in the power sharing among agencies at different levels of governance. Finally, this study suggests for developing future policies that support establishment of residential schools, individual education plan, transitional planning and individualized family service plans to enhance the promotion of disability sector in Nepal.